2022
DOI: 10.1002/advs.202200956
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Alterations in the Respiratory Tract Microbiota of Patients with COVID‐19 and its Association with Microbiota in the Gut

Abstract: The role of respiratory tract microbes and the relationship between respiratory tract and gut microbiomes in coronavirus disease 2019 (COVID‐19) remain uncertain. Here, the metagenomes of sputum and fecal samples from 66 patients with COVID‐19 at three stages of disease progression are sequenced. Respiratory tract, gut microbiome, and peripheral blood mononuclear cell (PBMC) samples are analyzed to compare the gut and respiratory tract microbiota of intensive care unit (ICU) and non‐ICU (nICU) patients and det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…In contrast, Mogibacterium , Lactococcus , and Bifidobacterium were significantly depleted in the surveyed COVID-19 patients compared with non-COVID patients and/or the local controls. Much lower level of Mogibacterium has been reported in COVID-19 patients requiring ICU ( 42 ); several species within the genera Lactococcus and Bifidobacterium play important roles in modulating innate cytokine and immune response, which potentially provides a protective benefit against COVID-19 if the naso-oropharyngeal microbiota approximating healthy condition is restored ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Mogibacterium , Lactococcus , and Bifidobacterium were significantly depleted in the surveyed COVID-19 patients compared with non-COVID patients and/or the local controls. Much lower level of Mogibacterium has been reported in COVID-19 patients requiring ICU ( 42 ); several species within the genera Lactococcus and Bifidobacterium play important roles in modulating innate cytokine and immune response, which potentially provides a protective benefit against COVID-19 if the naso-oropharyngeal microbiota approximating healthy condition is restored ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“… 33 , 34 Similarly, the critical role of the intestinal microbiome in both acute SARS-CoV-2 infections and long COVID has been widely reported, although the mechanisms behind it are still unclear. 12 , 13 , 14 , 17 , 35 , 36 , 37 One of the possibilities is through the intestinal epithelium for their importance in balancing the microbial community, as previously reported that gut microbiome dysbiosis induced by SARS-CoV-2 in mice was correlated with alterations to Paneth cells and goblet cells and markers of barrier permeability. 37 The group from Hong Kong reported that gut dysbiosis could persist for six months and one year in patients with long COVID with significantly lower bacteria diversity and richness and distinctly separated beta diversity.…”
Section: Gi Microbiome and Metabolites In Long Covidmentioning
confidence: 99%
“… 8 , 10 , 11 , 12 The critical role of the intestinal microbiome in these GI symptoms and long COVID were also reported in clinical patients or animal models. 12 , 13 , 14 …”
Section: Long Covidmentioning
confidence: 99%
“…After removing duplicate studies, screening the title and abstract, and performing a full-text assessment according to the eligibility criteria, 27 studies were finally included in this systematic review (Figure 1). Of the 27 studies, 18 studies compared only COVID-19 patients and HCs, [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] six compared only recovered COVID-19 patients and HCs, [25][26][27][28][29][30] and three compared both COVID-19 and recovered COVID-19 patients to HCs [31][32][33] (Table 1, Tables S3 and S4). Twenty-two studies were conducted in Asia (17 in China [including 4 in Hong Kong SAR], two in Japan, and one each in United Arab Emirates, India, and Bangladesh), while five others were 1, Table S5).…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%